2019
DOI: 10.3389/fphys.2019.01074
|View full text |Cite
|
Sign up to set email alerts
|

Fibro–Adipogenic Progenitors Cross-Talk in Skeletal Muscle: The Social Network

Abstract: Skeletal muscle is composed of a large and heterogeneous assortment of cell populations that interact with each other to maintain muscle homeostasis and orchestrate regeneration. Although satellite cells (SCs) – which are muscle stem cells – are the protagonists of functional muscle repair following damage, several other cells such as inflammatory, vascular, and mesenchymal cells coordinate muscle regeneration in a finely tuned process. Fibro–adipogenic progenitors (FAPs) are a muscle interstitial mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 105 publications
(184 reference statements)
4
172
0
4
Order By: Relevance
“…Ctgf and Pdgfc were also increased in the DIA, both of which can alone induce fibrosis through up‐regulation of ECM proteins and pro‐inflammatory factors . This fibrosis‐related expression profile in the DIA is suggestive of expansion of fibro/adipogenic progenitors (FAPs), which are the predominant source of ECM‐protein expression following injury and inflammation in skeletal muscle . Furthermore, expression of IL‐33, predominantly secreted by FAPs in skeletal muscle, is also increased in PDX DIA .…”
Section: Resultsmentioning
confidence: 96%
“…Ctgf and Pdgfc were also increased in the DIA, both of which can alone induce fibrosis through up‐regulation of ECM proteins and pro‐inflammatory factors . This fibrosis‐related expression profile in the DIA is suggestive of expansion of fibro/adipogenic progenitors (FAPs), which are the predominant source of ECM‐protein expression following injury and inflammation in skeletal muscle . Furthermore, expression of IL‐33, predominantly secreted by FAPs in skeletal muscle, is also increased in PDX DIA .…”
Section: Resultsmentioning
confidence: 96%
“…The reduced interstitial fibrosis and adipocyte accumulation in regenerating skeletal muscles of the HF‐ compared to NC diet‐fed mice is another potentially important finding, considering the prominence of these features in the ischaemic myopathy that is prevalent in PAD patients . These pathological outcomes could involve a subgroup of muscle‐resident stromal cells, fibro/adipogenic progenitors (FAP), which can differentiate into collagen‐secreting and/or adipocytes, contributing to fibrosis and inter‐myofibre fat deposition . We speculate that less FAP differentiation contributed to the lower extent of adipocyte accumulation and fibrosis observed in regenerating muscles of HF diet‐fed mice.…”
Section: Discussionmentioning
confidence: 93%
“…The muscle contains different progenitor cells, which include the myogenic progenitors, satellite cells, PW1+ progenitor cells, and fibro-adipogenic progenitor cells (FAPs) [1]. In the healthy skeletal muscle, a balance is maintained between these myogenic progenitors and the FAPs, and the FAPs are believed to aid in muscle regeneration [28,29]. Kozlowska et al showed that MSCs from the healthy skeletal muscles have the limited adipogenic potential [30], and Marinkovic et al showed that seeding purified skeletal muscle stem cells and FAPs in co-culture at a 1: 1 ratio inhibits lipid droplet formation even under adipogenic conditions [31].…”
Section: Discussionmentioning
confidence: 99%